Place of Culture in Curriculum Planning in Nigeria Tertiary Institutions - MUSA H.A (International Studies Journal)
Culture, Curriculum ,and education are viewed from different angles but the main focus of this work is the position of culture in curriculum planning in Nigeria tertiary institutions .This paper argues that curriculum cannot stands on its own without considering the culture of the society since curriculum is being planned for the students and his environs .The key concept of culture ,curriculum and its planning are explained while tertiary education was also explained in line with national policy on education. The paper went ahead discussing objectives of curriculum planning as a basic tool for higher education system in order to achieve the educational goals requirements necessary for students' success across and entire curriculum. And also stated that Nigeria culture plays an important role in the lives of separate individuals and the society as a whole. The paper fully discusses the place of culture in curriculum Planning at Tertiary Education in Nigeria, as well as some necessary way forward on how to strengthen Nigeria education and its curriculum.